The MaNGA Dwarf Galaxy Sample (MaNDala): Stellar Profiles and Gradients Characterization - M. Cano-Díaz; A. Rodríguez-Puebla; A. C. Robleto-Orús; V. Ávila-Reese; H. M. Hernández-Toledo; J. A. Vázquez-Mata; O. Valenzuela; J. J. González; H. J. Ibarra-Medel; J. C. Clemente-González; L. Pavón-Alvarez (The Astronomical Journal)
We derived robust radial profiles and inner/outer gradients of various stellar population (SP) properties for a sample of 124 bright dwarf galaxies, 10 ^7.53 ≤ M _* / M _⊙ ≤ 10 ^9.06 , from the MaNDala sample, using integral field spectroscopy observations. Given the complex structure of dwarf galaxies, we explored four different methods to derive SP radial profiles: two based on concentric elliptical rings, and the other two exploiting the spatially resolved nature of the data. For each method, we applied four approaches to calculate the following inner (0 ≤ R / R _e ≤ 1) and outer (0.75 ≤ R / R _e ≤ 1.5) gradients: luminosity- and mass-weighted age and stellar metallicity, dust attenuation, D _n _4000 index, stellar mass and star formation rate (SFR) surface densities, and specific SFR. While the point-spread function has a minor impact on the SP gradients, the choice of methodology for characterizing radial profiles significantly affects them. At fixed property, differences in inner gradients from concentric rings methods are typically ∼0.05–0.1 dex R _e ^−1 , while outer gradients can reach 0.5–1 dex R _e ^−1 , relative to the median of all gradients of that property, $\,\rm{med}\,\left({\{{\rm{\nabla }}\,{ \mathcal G }\}}_{i}\right)$ . Spatially resolved methods yield smaller differences, ≲0.1 dex R _e ^−1 . For some SP gradients, such as ∇ _SFR , the dispersion among the methods is comparable to $\,\rm{med}\,\left({\{{\rm{\nabla }}\,{ \mathcal G }\}}_{i}\right)$ . While it is not possible to select a single preferred method for determining SP gradients, we suggest using $\,\rm{med}\,\left({\{{\rm{\nabla }}\,{ \mathcal G }\}}_{i}\right)$ for each SP property. The resulting median age and metallicity suggest that, overall, bright dwarfs experienced moderate inside-out formation, accompanied by significant early SF from low-metallicity gas with outward radial migration of old SPs. The derived SP gradients provide strong constraints on feedback mechanisms in dwarf galaxies.